Transplantation of Adipose-Tissue-Engineered Constructs with CRISPR-Mediated UCP1 Activation - Michurina, Svetlana; Stafeev, Iurii; Boldyreva, Maria; Truong, Vu Anh; Ratner, Elizaveta; Menshikov, Mikhail; Hu, Yu-Chen; Parfyonova, Yelena (International journal of molecular sciences, 2023)
Thermogenic adipocytes have potential utility for the development of approaches to treat type 2 diabetes and obesity-associated diseases. Although several reports have proved the positive effect of beige and brown adipocyte transplantation in obese mice, translation to human cell therapy needs improvement. Here, we describe the application of CRISPR activation (CRISPRa) technology for generating safe and efficient adipose-tissue-engineered constructs with enhanced mitochondrial uncoupling protein 1 (UCP1) expression. We designed the CRISPRa system for the activation of UCP1 gene expression. CRISPRa-UCP1 was delivered into mature adipocytes by a baculovirus vector. Modified adipocytes were transplanted in C57BL/6 mice, followed by analysis of grafts, inflammation and systemic glucose metabolism. Staining of grafts on day 8 after transplantation shows them to contain UCP1-positive adipocytes. Following transplantation, adipocytes remain in grafts and exhibit expression of PGC1α transcription factor and hormone sensitive lipase (HSL). Transplantation of CRISPRa-UCP1-modified adipocytes does not influence glucose metabolism or inflammation in recipient mice. We show the utility and safety of baculovirus vectors for CRISPRa-based thermogenic gene activation. Our findings suggest a means of improving existing cell therapy approaches using baculovirus vectors and CRISPRa for modification and transplantation of non-immunogenic adipocytes.